META-ANALYSIS: VALIDITY AND PRACTICALITY OF DEVELOPING BIOLOGY PRACTICUM GUIDEBOOK ON INDEPENDENT CURRICULUM - Restu Ibunda, Masyithoah; Zulyusri (Universitas Negeri Semarang, 2024)
The independent curriculum is a government program aimed at optimizing education and preparing to face the challenges of the Scientific 5.0 era which emphasizes the learning process on character building, critical thinking and project assignments that make students more challenged in learning. One important aspect of biology learning is practicum activities. Practicum activities can help students think, analyze, solve problems, prove and draw conclusions about matters related to certain subjects. Practicum activities require a guide in the form of a practicum guide in order to make it easier for students to carry out experimental steps. This study aims to analyze the validity and practicality of the biology practicum guidebook of the independent curriculum. This study used meta-analysis techniques with data collection through the collection of articles or journals via the internet. The sample used was 10 articles related to the use of biology practicum guidebooks. The results found the level of validity of using practicum guides with an average of 89.6%, then the level of practicality of using practicum guides with an average of 87.7%. Thus, the use of practicum guides can be categorized as valid and practical so that the development of independent curriculum biology practicum guides can be carried out.